Developing a numerical model to analyze the production process of PMEDM. (January 2023) - Rajkumar, G.; Saravanan, M.; Marimuthu, P.
Abstract: Production process optimization has been considered as one of the essential elements in modern metal mines context. Several operations were started to modify with these resources concern, which mainly includes machining processes. Various technological developments have been evident in these machining processes including electrical discharge machining. However, due to several limitations of conventional process, powder mixed discharge machining has been brought into the research realm. Recent years, many applications can be found under the mining sector. Despite of various perspectives have been considered but concerning with increase of mining process through optimizing its parameters are limited. In this study, this literature gap has been addressed, with the consideration of optimizing the production process parameters optimization of metal mines, in which concentrations of the reinforcements and peak current are considered as input parameters. The performance of the proposed parameters has been measured with the outputs including surface quality, surface roughness, material removal rate and tool wear rate. Various behavior analysis was done to identify the effective process parameters with resource optimization objective. Totally, ten different combination of process parameters were studied through numerical analysis in addition with experimental studies. Finally, the results revealed that PP2 is the best process parameter for achieving better performance. Further, the necessary future direction to explore more scientific potential on the concern topic has been discussed. Highlights: Optimizing the production process parameters optimization of metal mines. Behavior analysis was performed to identify the effective process parameters. Various combinations of process parameters were studied through numerical analysis.